(untitled) (International Journal of Engineering Sciences & Management Research, 2017)
Now a days in packaging industry for paper sticking strip gumming machine is used but in such machine material handling is more. Release paper cannot reused to overcome that we construct a machine which reduces cycle time, increases productivity and less human effort are required due to that the overall profit is increases, less labour are required and manufacturing time is decreases. In the manufacturing of labals, posters,and the like, it is a frequently desirable to gum portion only of one face of the label or poster and to leave the reminder of the gummed side of the strip in an un gum condition